2017
DOI: 10.1515/intox-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to quinalphos shows biochemical changes and genotoxicty in erythrocytes of silver barb, Barbonymus gonionotus

Abstract: An in vivo study was carried out on the freshwater fish Barbonymus gonionotus to evaluate the genotoxic effects of the organophosphate quinalphos. The fish were exposed to sub-lethal doses of quinalphos (0%, 10%, 25%, and 50% of LC50) for a period of 30 days. Analysis of biochemical characteristics (protein and lipid contents of different organs), nuclear abnormalities of erythrocytes (NAE) and morphological abnormalities of erythrocytes (MAE) were performed on peripheral erythrocytes sampled at post-treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, Al-Obaidi and Al-Shawi [72] reported findings similar to our results; they reported that FLX has genotoxic potential and can induce MN in polychromatic erythrocytes in the bone marrow of male rats. However, the origins of these morphological alterations of the nucleus have been found to arise from genotoxic events caused by exposure to xenobiotic agents [73] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Al-Obaidi and Al-Shawi [72] reported findings similar to our results; they reported that FLX has genotoxic potential and can induce MN in polychromatic erythrocytes in the bone marrow of male rats. However, the origins of these morphological alterations of the nucleus have been found to arise from genotoxic events caused by exposure to xenobiotic agents [73] .…”
Section: Discussionmentioning
confidence: 99%
“…Dacrocyte (Da, Tr): [4,47,77,87,96,129,140,152,153]. Schistocyte (Sch, Sh): [5,69,77,130,154,155]. Codocyte (C): [44,93].…”
Section: Acanthocytementioning
confidence: 99%
“…Despite extensive usage of quinalphos in agriculture for control of pests over crops, inhibition of acetylcholinesterase (AChE) was reported in non-target organisms by quinalphos (Chebbi and David, 2009;Kopecka et al, 2004;Pan and Dutta, 1998;Silman and Sussman, 2005;Vig et al, 2006). Quinalphos adversely influence on blood and brain esterase activity in chickens (Vairamuthu and Thanikachalam, 2003), fish fertility efficiency in adult male rats (Sarkar et al, 2000) and also genotoxicity to silver barb (Sadiqul et al, 2017). A 3-year (2000)(2001)(2002) evaluation report (Teixeira et al, 2004) of forensic pesticide and herbicide intoxications in Portugal indicated about 29% of total cases due to quinalphos.…”
Section: Quinalphos and Its Metabolite -2-hq Toxicitymentioning
confidence: 99%